MORAL VALUES FOUND IN THE NOVEL ENTITLED “LITTLE FIRES EVERYWHERE” BY CELESTE NG - Dian Novita (Universitas Jambi, 2019)
This study investigates moral values in the Little Fires Everywhere novel by Celeste Ng. The researcher investigates moral values through novels because today the moral crisis also occurs in the world of education. Researchers want to find out whether they can learn moral values through the novel or not. Based on the investigation, researchers used novels to find moral values. The classification of moral values has concerned with motherhood, bravery, love, togetherness, honesty, independent, discipline, wise, and diligent. The researcher concludes that the findings suggest that some moral values can be learned in the novel entitled Little Fires Everywhere by Celeste Ng.